Vital Relationships: Classroom as an Ongoing Research Setting (2014)
This paper considers the potential research has in transforming subjects and their knowledge, and for this, it finds in education a possibility of growing and being acknowledged, from diverse categories, as a formative strategy and as a tool required in the responsibility a professional has with both his/her discipline and the knowledge generation. Based on this, the characteristic elements of a teacher’s day-to-day work are analyzed, defining in this way (a) Pedagogy as a guide in human being formation, (b) Didactics as a set of strategies designed for an impartial relationship between teaching and learning, strengthening the studentteacher relationship, (c) Curricula as the organization, prioritization and analysis of the knowledge flowing in the classroom, and (d) Evaluation as an assessment element of the whole process to redefine it. Finally, the conjunction of these elements with the research structural aims is explained to generate one of many proposals, that supports teachers in their decision to research, which does not mean wasting time or available resources.